2021
DOI: 10.1002/adma.202008752
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Covalent Bonds Regulated Electron‐Deficient 2D Black Phosphorus for Electrocatalytic Oxygen Reactions

Abstract: Developing resource‐abundant and sustainable metal‐free bifunctional oxygen electrocatalysts is essential for the practical application of zinc–air batteries (ZABs). 2D black phosphorus (BP) with fully exposed atoms and active lone pair electrons can be promising for oxygen electrocatalysts, which, however, suffers from low catalytic activity and poor electrochemical stability. Herein, guided by density functional theory (DFT) calculations, an efficient metal‐free electrocatalyst is demonstrated via covalently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…[51,52] After modified by metallic Ir species, it is clearly identified that the first peak in BPIr_sur (A") and BPIr_be catalysts (A") become less obvious and the second peaks (B" and B") shift toward low energies, suggesting the partial suppression on the oxidation degree of the BP surfaces, accompanied by the possible formation of metalphosphorus bonds that are favorable for structural stability. [53,54] Then, a broad peak at ≈2167.0 eV clearly appears in Adv. Mater.…”
Section: Surface-dependent Catalytic Enhancement Mechanismmentioning
confidence: 99%
“…[51,52] After modified by metallic Ir species, it is clearly identified that the first peak in BPIr_sur (A") and BPIr_be catalysts (A") become less obvious and the second peaks (B" and B") shift toward low energies, suggesting the partial suppression on the oxidation degree of the BP surfaces, accompanied by the possible formation of metalphosphorus bonds that are favorable for structural stability. [53,54] Then, a broad peak at ≈2167.0 eV clearly appears in Adv. Mater.…”
Section: Surface-dependent Catalytic Enhancement Mechanismmentioning
confidence: 99%
“…Rechargeable zinc-air batteries (ZABs) are widely considered as one of the most promising energy storage devices, owing to their high specific energy density (1084 Wh kg À 1 ), unique semi-closed systems, low cost, and environmentally friendly nature (Scheme 1). [39,40] There are two main avenues for the development of ZABs: electrochemical cells based on either aqueous alkaline or aprotic electrolytes. [41] For water-based electrolytes, their low energy efficiency is a fundamental problem.…”
Section: Rechargeable Zinc-air Batteriesmentioning
confidence: 99%
“…Great progress has been made in the development of bifunctional electrocatalysts for these processes. [39,40,[42][43][44][45][46] Moreover, fundamental problems on the Zn anode side must be addressed. [47] Firstly, the corrosion of the Zn anode is a parasitic reaction, in which Zn reacts with water to produce zinc hydroxide (Zn(OH) 2 ) or, in alkaline solution, [Zn(OH) 4 ] 2À and hydrogen gas.…”
Section: Rechargeable Zinc-air Batteriesmentioning
confidence: 99%
See 2 more Smart Citations